Engineering the Future of Education: Integrating Curriculum and Technology in Indonesia's Digital Age - Gagarin, Yuri; Zaskiyah Veronica; Sinta Adili; Intan Nur Fadillah; Akbar Dieva; Mardiah Astuti (International Journal of Asian Education, 2025)
The rapid digital transformation has placed education as a crucial sector requiring curriculum-technology integration to prepare Indonesian human resources for global competition. This study aims to examine curriculum and technology integration as a strategy for engineering Indonesian education in the digital era. Using a convergent mixed methods design parallel to library research, the study targeted educators, students, parents, and policymakers in urban, rural, and 3T areas (N=395; n=350 surveys, n=45 interviews, 6 focus groups). Instruments included validated questionnaires, semi-structured interviews, and focus group guides, analyzed using SPSS descriptive statistics and NVivo thematic coding with data triangulation. Results showed an 82% increase in student engagement and 76% increase in digital literacy through blended learning, despite infrastructure gaps (42% fast internet) and teacher training deficits (62%). Conclusions emphasize content localization, TPACK training, and stakeholder collaboration for inclusive digital transformation aligned with the Independent Curriculum.